2022
DOI: 10.1101/2022.10.07.511265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophila epidermal cells are intrinsically mechanosensitive and drive nociceptive behavioral outputs

Abstract: Somatosensory neurons (SSNs) that detect and transduce mechanical, thermal, and chemical stimuli densely innervate an animal's skin. However, despite the fact that epidermal cells provide the first point of contact for sensory stimuli. our understanding of roles that epidermal cells play in SSN function, particularly nociception, remains limited. Here, we show that stimulating Drosophila epidermal cells elicits activation of SSNs including nociceptors and triggers a variety of behavior outputs, including avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…, 2018 ; Mikesell et al. , 2022 ; Yoshino et al. , 2022 ): Chemo- or optogenetic activation of keratinocytes promotes sensory afferent firing and nocifensive behaviors, while electrically silencing keratinocytes attenuates these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…, 2018 ; Mikesell et al. , 2022 ; Yoshino et al. , 2022 ): Chemo- or optogenetic activation of keratinocytes promotes sensory afferent firing and nocifensive behaviors, while electrically silencing keratinocytes attenuates these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, nociceptors would exhibit heightened sensitivity to epidermal ion flux, and recent studies indicate that epidermal stimulation influences response properties of SSNs including Drosophila nociceptors (82)(83)(84). However, we found that mutation of the mechanosensory channel gene Piezo decoupled dendrite intercalation and mechanical hypersensitivity.…”
Section: Discussionmentioning
confidence: 53%
“…Second, epidermal dendrite intercalation could facilitate nociceptor activation through enhanced ionic coupling to epidermal cells, analogous to lateral excitation that improves motion sensitivity of ON bipolar cells [87]. In such a case, nociceptors would exhibit heightened sensitivity to epidermal ion flux, and recent studies indicate that epidermal stimulation influences response properties of SSNs including Drosophila nociceptors [88][89][90]. However, we found that mutation of the mechanosensory channel gene Piezo decoupled dendrite intercalation and mechanical hypersensitivity.…”
Section: Plos Geneticsmentioning
confidence: 76%